Conservative Approach in Patients with Pemphigus Gingival Vulgaris: A Pilot Study of Five Cases. (20th November 2014) - Gambino, Alessio; Carbone, Mario; Arduino, Paolo G.; Carcieri, Paola; Carbone, Lucio; Broccoletti, Roberto
Abstract : Objectives . The aim of this pilot study was to describe the clinical efficacy of a conservative oral hygiene protocol in patients affected by gingival pemphigus vulgaris (PV) applied in a case series. Methods . Subjects suffering from PV with gingival localisation and slightly responsive to conventional treatment with systemic corticosteroids and immunosuppressive drugs were selected among individuals treated in the Unit of Oral Medicine Section of the University of Turin. Five subjects received nonsurgical periodontal therapy, over a 7-day period, including oral hygiene instructions; patients were instructed about domiciliary oral hygiene maintenance and instructions were reinforced at each visit and personalised if necessary. Clinical outcome variables were recorded at baseline (before starting) and 16 weeks after intervention, including full mouth plaque score (FMPS), bleeding scores (FMBS), probing pocket depth (PPD), oral pemphigus clinical score (OPCS), and patient related outcomes (visual analogue score of pain). Results . Five patients were treated and, after finishing the proposed therapy protocol, a statistical significant reduction was observed for FMBS (P = 0.043 ) and OPCS (P = 0.038 ). Conclusions . Professional oral hygiene procedures with nonsurgical therapy are related to an improvement of gingival status and a decrease of gingival bleeding in patients affected by PV with specific gingival localization.